RESPON PENGGUNAAN FAKTOR PRODUKSI PADA USAHATANI PADI GOGO - Aliudin, Aliudin (Jurnal AGRISEP, 2011)
Conversion of agricultural land to non agricultural land can not be avoided, while the needs of  rice continues to grow. To  meet these needs , efforts to develop upland rice are needed. Upland rice can be grown on dry land, moor, or former forest land with minimal irrigation (rainfed). In general, farmers use the production factors  uncontrolable, making it difficult to estimate the response of the use of production factors . Based on the research conducted in  Cimarga Subdistrict Lebak District   in 2010 plant season. This study aims to estimate the  response of factors use on upland rice production. Thirty upland paddy farmers were selected using Simple Random Sampling dan Cobb – Douglas Model of upland paddy production was applied to analyse production factors response.   The results showed: (a) a partial response acreage and volume of urea fertilizer on upland paddy farming is positive, while the number of labor and seed volume showed a negative effect (b) Simultaneously the four factors of production toward upland paddy production has a positive effect.  Seed acreage and volume showed a positive response to the production of upland rice  indicate that farmers  still have a chance to increase  acreage and  seed use. On the contrary, the use of labor and fertilizer urea showed a negative response indicating that the use of these two production factors  have already excessively, and farmers have to reduce the use of these production factors.  Key words : production factors, farming, paddy of dry land